ON THE INCIDENTAL FISHERY OF SKATES AND RAYS OFF CALICUT - Devadoss, P (Indian Journal of Fisheries, 2011)
The total skates and rays landed as incidental components by the three maingears, trawl net, drift net and hooks-and-lines, accounted for 70.9 t, forming 10%of the total elasmobranch landings of Calicut during 1977-80. The most commonspecies of rays were the sting rays, spotted eagle-ray, and the devil-ray, and theskate, R. djeddensis. The trawlers alone landed 95%. The trends of effort, catch andcatch rate, examined for the 10-year period 1971-1980, showed that during the earlierhalf both catch and CPUE had a general upward trend, the former reaching the alltimehigh of 64 t in 1974 followed by the latter reaching the maximum of 11.9 kg perstandard effort in 1975, after which both had descended down steadily to the alltimelow of 1980, with clear negative response to effort, indicating the probabilitythat the stock in the area could not stand the type of effort that was put in 1974-75.The reasons peculiar to this elasmobranch group contributing to its easy depletionare pointed out.